Factors associated with oxygenation improvement in children with ARDS - Abdul Chairy; Nurnaningsih Nurnaningsih; Endy P. Prawirohartono (Paediatrica Indonesiana, 2014)
Background In pediatric patients, acute respiratory distresssyndrome (ARDS) has a high mortality rate of approximately25%. In surviving children, ARDS may result in sequelae, suchas restrictive or obstructive lung dysfunction, muscle weaknessand hypotrophy, as well as psychiatric, intelligence, and memoryproblems.Objective To identify prognostic factors related to oxygenationimprovement in children with ARDS.Methods We conducted a prospective cohort study in the pediatricintensive care unit (PICU) ofSardjito Hospital, Yogyakarta.We included 20 children aged 29 days to 18 years who fulfilled theARDS criteria. They underwent lung recruitment maneuver for1 hour. Logistic regression analysis was used to assess for possibleassociations between potential prognostic factors and oxygenationimprovement.Results None of the subjec ts had significant hemodynamicchanges or hypercapnea during lung recruitment. Two prognosticfactors from our univariate analysis, namely type of ARDS (RR0.17; 95% CI 0.023 to 1.23; P= 0.079) and severity of ARDS(RR 0.74; 95% CI 0.007 to 0.84) , were analyzed by multivariatelogression test. However, the results were not statisticallysignificant for type of ARDS (RR 0.33; 95% CI0.009 to 1.41) orseverity of ARDS (RR 0.11; 95%CI 0.009-3.25).Conclusion We do not identify any prognostic factors, includingtype and severity of ARDS, associated with oxygenationimprovement in children with ARDS.